In situ synthesis of visible-light-driven Z-scheme AgI/Bi2WO6 heterojunction photocatalysts with enhanced photocatalytic activity. Issue 5 (1st April 2019) - Xue, Wenjing; Peng, Zhiwei; Huang, Danlian; Zeng, Guangming; Wen, Xiaoju; Deng, Rui; Yang, Yang; Yan, Xuelei
Abstract: In this work, an efficient visible-light-response AgI/Bi2 WO6 heterojunction was successfully prepared via in situ precipitation of AgI nanoparticles on the aligned nanosheets of three-dimensional Bi2 WO6 hierarchical microspheres for the first time. Studies suggested that the AgI/Bi2 WO6 heterojunction exhibited excellent photocatalytic activity for tetracycline (TC) degradation compared to pure Bi2 WO6 and AgI under visible light irradiation. Doping 20 wt% AgI resulted in the optimal TC photodegradation rate, which was 5.4 and 3.3 times higher than pure Bi2 WO6 and AgI, respectively. The high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) verified that Ag nanoparticles generated on AgI/Bi2 WO6 heterojunction surface in photocatalytic degradation process, which was beneficial for promoting the rapid combination of electrons on the conduction band of Bi2 WO6 with the holes on the valence band of AgI and the separation and transfer of photogenerated electron-hole pairs. Accordingly, the nontraditional transport pathway of photogenerated electrons and holes based on the Z-scheme system that consisted of Bi2 WO6, AgI, and Ag was confirmed. Based on the systematic experimental evidence, the possible enhanced photocatalytic mechanism was proposed.